ANALISIS PENERAPAN KNOWLEDGE MANAGEMENT PADA LEMBAGA PENDIDIKAN MENENGAH: STUDI KASUS DI SMPI AINUL ULUM SUNGAI AMBAWANG - Abdullah Rizki Ramadhan; Sugeng Listyo Probowo (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of knowledge management at SMPI Ainul Ulum Sungai Ambawang through four main management functions: planning, organizing, implementing, and supervising. The study used a qualitative descriptive approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The collected data were analyzed using the Miles and Huberman model through the stages of reduction, presentation, and drawing conclusions with triangulative verification. The research findings indicate that the planning function is realized through annual plenary forums and weekly meetings that produce lesson plans as a reference for learning implementation. The organizing function includes structuring the organizational structure, dividing tasks and authorities, and establishing activity committees supported by the principal's supervision. The implementation function focuses on the process of knowledge transfer between teachers and students through adaptive learning strategies. The supervisory function is implemented through two-way performance evaluations involving the principal and educators to ensure the achievement of learning objectives.